The stratospheric QBO signal in the NCEP reanalysis, 1958-2001 - García Herrera, Ricardo Francisco; Calvo Fernández, Natalia; Gallego, David; Hernández Martín, Emiliano; Gimeno, Luis; Ribera, Pedro; Peña Ortiz, Cristina (American Geophysical Union, 2003)
© 2003 by the American Geophysical Union. The spatiotemporal evolution of the zonal wind in the stratosphere is analyzed based on the use of the NCEP reanalysis (1958-2001). MultiTaper Method-Singular Value Decomposition (MTM-SVD), a frequency-domain analysis method, is applied to isolate significant spatially-coherent variability with narrowband oscillatory character. A quasibiennial oscillation is detected as the most intense coherent signal in the stratosphere, the signal being less intense in the lower levels. There is a clear downward propagation of the signal with time at low latitudes, not evident at mid and high latitudes. There are differences in the behavior of the signal over both hemispheres, being much weaker over the SH. In the NH an anomaly in the zonal wind field, in phase with the equatorial signal, is detected at approximately 60degreesN. Two different areas at subtropical latitudes are detected to be characterized by wind anomalies opposed to that of the equator. Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub